2016
DOI: 10.1016/j.fuel.2015.10.120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal catalytic deoxygenation of palmitic acid over nickel catalyst

Abstract: Fatty acid has recently received considerable interest as a possible precursor for producing renewable hydrocarbon. In this study, we investigated hydrothermal catalytic deoxygenation of palmitic acid to produce paraffin over a Ni/ZrO 2 catalyst with no or low-pressure (100 psi) external supply of H 2. The results show that the presence of water greatly improved conversion of palmitic acid and paraffin yield. Significant improvement was attributed to the formation of in-situ H 2. Without an external H 2 supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 39 publications
9
67
1
3
Order By: Relevance
“…When the Fe 2 O 3 / MCM-41 magnetic catalyst was employed, the maximum conversion of palmitic acid was 68.1% at 342 C, while that of Fe 2 O 3 /Al-MCM-41 reached 77.4% at 350 C. During fatty acid deoxygenation, the desired product had one less carbon than the corresponding acid. [33][34][35] In addition to deoxygenation reactions, a series of reactions could happen spontaneously on the Fe 2 O 3 /MCM-41 catalyst. These transformations mainly involved isomerization, cracking, hydrogenation, and cyclization reactions.…”
Section: Fe 2 O 3 /(Al-)mcm-41 For the Catalytic Decarboxylation Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…When the Fe 2 O 3 / MCM-41 magnetic catalyst was employed, the maximum conversion of palmitic acid was 68.1% at 342 C, while that of Fe 2 O 3 /Al-MCM-41 reached 77.4% at 350 C. During fatty acid deoxygenation, the desired product had one less carbon than the corresponding acid. [33][34][35] In addition to deoxygenation reactions, a series of reactions could happen spontaneously on the Fe 2 O 3 /MCM-41 catalyst. These transformations mainly involved isomerization, cracking, hydrogenation, and cyclization reactions.…”
Section: Fe 2 O 3 /(Al-)mcm-41 For the Catalytic Decarboxylation Of Amentioning
confidence: 99%
“…shows the XRD patterns of the prepared Fe 2 O 3 /MCM-41 and Fe 2 O 3 /Al-MCM-41 catalysts. In the large-angle range, the diffraction peaks at 31.66 ,35.56 , 43.28 , and 57.36 are attributed to the (220), (311), (400), and (511) reections of maghemite (g-Fe 2 O 3 ; referenced to JCPDS 25-1402) 27,28. Mineral clinoptilolite was employed as an aluminum source.…”
mentioning
confidence: 99%
“…We are unaware of any reports on catalytic hydrothermal deoxygenation of TAG over nickel supported on carbon (Scheme ). However, there have been related studies that involved nickel (Miao et al, ; Yang et al, ). For instance, Miao et al, reported the formation of renewable hydrocarbons over nickel supported on ZrO 2 under low external H 2 pressure (100 psi) in a hydrothermal medium (Miao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been related studies that involved nickel (Miao et al, ; Yang et al, ). For instance, Miao et al, reported the formation of renewable hydrocarbons over nickel supported on ZrO 2 under low external H 2 pressure (100 psi) in a hydrothermal medium (Miao et al, ). It was shown that the use of water improved conversion of palmitic acid to 64.7C % as opposed to just 17.2C % achieved in the absence of water.…”
Section: Introductionmentioning
confidence: 99%
“…Various catalysts have been investigated in different types of reactors (batch and continuous) to upgrade different fatty acids and vegetable oils such as carbon based catalysts [14,15], Nickel supported catalysts (NiZrO2) [16] and noble metal based catalysts supported on carbon (Pd/C and Pt/C) [7,17]. However, acidic catalysts such as zeolites have been shown to be more suitable for producing lighter fractions from lipids.…”
Section: Introductionmentioning
confidence: 99%